Agrifood chain toolkit conference, Kampala, Uganda: Quick comments from participants - International Livestock Research Institute (International Livestock Research Institute, 2013)
This film shares participant's comments from the Agrifood chain toolkit conference, which was held in Nairobi Kenya 9-11 September, 2013. The meeting was co-hosted by CGIAR Research Programs Livestock and Fish & Policies, Institutions and Markets.